Leveraging Geographic Information Systems for Polio Surveillance and Eradication: A Systematic Review - Salmana Ahmed; Mohammad Imran; Shafi Ullah; Shanila Azhar; Mohammad Ashraf; Raja Zahilah (Universitas Airlangga, 2026)
Background: The eradication of Polio virus is one of the important public health issues. In order to remove this virus, some well-planned methods are required. Objective: The aim of this paper is to assess GIS usage in different aspects of surveillance of polio virus. Specifically, the focus of this research is GIS applications, their practical challenges, and limitations in the context of polio viruses. Methods: Based on the systematic review of 36 peer reviewed studies across several academic research databases, we evaluated how GIS is used in polio control and eradication. Results: The findings include applications of GIS in several aspects. Few of these include vaccination coverage, analysis of disease patterns, and integration with existing healthcare information networks. Moreover, several important obstacles were also identified in context of shortcomings of data, infrastructure and expertise. Conclusion: The findings of this study offer useful guidance for healthcare workers and policymakers involved in eradication of polio viruses. Keywords: Challenges, Geographic Information Systems (GIS), Polio virus, Surveillance, Systematic Review